The perspective of ESP teaching: a study of english subject for undergraduate nursing students at Hafshawaty University - Islam, Raudhatul (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
This study aimed to determine the perspective of ESP teaching on undergraduate nursing students at Hafshawaty University, Probolinggo, East Java. This research used qualitative methods, data were collected through questionnaires, interviews and documentation. The subjects of this study were seven undergraduate nursing students at Hafshawaty University (i.e. m1, m2, m3, m4, m5, m6 and m7) who were asked to fill in questions related to ESP teaching in their programmes and one English lecturer to be interviewed in this research. These undergraduate nursing students were selected because they were eager to learn English related to their programme and lecturer who are selected based on their expertise. The results showed that the material taught was beyond their ability level and could not be easily understood, but with the group work system, the material taught by the lecturer made the undergraduate nursing students understand it and were enthusiastic about learning English in the ESP class.